Castles in the Air: Vision and Narrativity in Julien Green's Minuit - Robert Ziegler (Studies in 20th & 21st Century Literature, 1992)
One feature of Julien Green's 1936 novel Minuit is its examination ofthe problematical relationship between narrative discourse and its receiver. In the text, various characters act as narrators who order and assign a temporal structure to real or fictive events and rely on a narratee's receptivity to discover the meaning intended. In view of the attention accorded in the text to the process of story-telling, one may conclude that Green intended his work to interrogate the nature of its own narrativity. In addition, Green's character, the enigmatic Edme, is a mystic by reason of language, evoking through speech in himself and in others a glimpse of ineffable "truths." In him is resolved the apparently insoluble conflict between religious seeker and narrator-esthete, thus legitimizing the work of the novelist Green, "a mystic who never ceased to repress the language of the poet." What remains to be answered is whether Edme emerges as a simple illusionist-charlatan or whether he is given the role of a narrator who can speak a metaphysical language. The argument of this essay is that rehabilitating what for Green is the epistemological function of narrative does not depend on designating as real or unreal the world to which narrative alludes, but on establishing a pact between the receiver and sender of a message whose truth is irrelevant.
Keywords: Julien Green; Minuit; relationship; narrative discourse; narrative; receiver; narrators; real; fictive; religious seeker; story-telling; enigmatic Edme; Edme; language; truths; narrator-esthete; narrator; metaphysical language; epistemological function; truth